Etnokimia dan Kearifan Lokal Pengawetan Ikan Asin Sibolga dalam Pembelajaran Kimia - Sari, Tria Ananda; Lisa, Novia; Azzahara, Salsabila; Hutabarat, Zulfan Fajri; Gultom, Bastian; Kriswantoro, Kriswantoro (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2026)
Ethnochemistry examines the relationship between cultural practices and modern chemical concepts, one of which is the preservation of salted fish by the people of Sibolga, North Sumatra. This study aims to analyze the local wisdom of salted fish preservation in relation to the concepts of osmotic pressure and food chemistry and its potential as a contextual chemistry learning. The research method uses a qualitative approach with a literature study design through searching and reviewing written sources, with the object of study being the salted fish preservation practices of the Sibolga people. Data were collected through documentation and analyzed using content analysis. The results of the study indicate that the process of salting and drying fish creates hypertonic conditions that trigger osmosis, reduce water content, inhibit the growth of microorganisms, and affect the texture and shelf life of the fish. The conclusion of the study shows that the salted fish preservation practices of the Sibolga people reflect the integration of local wisdom with modern chemical concepts and have the potential to be used as a source of local culture-based chemistry learning.